Cancer is overtaking cardiovascular disease as the main driver of socioeconomic inequalities in mortality: New Zealand (1981–99). Issue 1 (20th December 2006) - Fawcett, J; Blakely, T
Abstract : Background: Relative socioeconomic disparities in cardiovascular mortality have increased in New Zealand, as in many Western countries in Northern Europe, the US and Australia during the late 20th century. However, substantial declines in cardiovascular mortality mean that its absolute contribution to overall mortality has decreased. Research questions: How did the absolute contribution of major causes of death to socioeconomic inequalities in New Zealand change during the 1980s and 90s? Methods: Linked census–mortality cohorts were used to calculate the contribution of different causes of death to inequalities in mortality, measured with the slope index of inequality, by household income. Results: Between 1981–4 and 1996–9, the contribution of cardiovascular disease (CVD) to total inequality declined from 55% to 28% among women, whereas at the same time the contribution of cancers increased from 14% to 37%. Among men, the contribution of CVD to total inequality peaked at 47% in 1986–9, then declined to 38% in 1996–9. The contribution of cancer increased from 19% to 26% in men. Conclusion: CVD mortality has declined at all income levels and so too has the contribution of CVD to mortality inequalities. Concurrently, the contribution of cancer to inequalities in mortality by income has increased and, in women at least, is now greater than the contribution of CVD. It is hypothesised that a similar crossover is occurring in other populations where CVD mortality has declined, although socioeconomic differences in the distribution and effect of the obesity epidemic for CVD may ensure its continuing importance. Prevention efforts aimed at reducing socioeconomic inequalities in mortality will need to increasingly focus on socioeconomic inequalities in cancer mortality.